2022
DOI: 10.3390/ijerph19137686
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Blockchain Application on the Qualification Rate and Circulation Efficiency of Agricultural Products: A Simulation Analysis with Agent-Based Modelling

Abstract: In the context of COVID-19, the circulation of agricultural products is increasingly important for the nutrition and health of people. With the changing needs of society and the advancement of technology, the agricultural product circulation system needs to undergo corresponding changes to adapt to the modern fast-paced social system. Blockchain technology couples with the circulation of agricultural products, as its technical features, such as immutability and a distributed ledger database, ensures the speed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In the process of achieving the SDGs, the food supply chain still faces a number of challenges such as Blockchainembedded agricultural quality transparency, accountability, food scandals and inefficiencies in trust and information flow (Chandan et al, 2023). These issues affect consumers' trust in governments, certification bodies and food producers and their willingness to buy (Wang et al, 2022). Numerous scholars have studied the improvement of agricultural product quality by financial credit regulation such as green finance and agricultural credit.…”
Section: Credit Supervision Of Agricultural Product Quality and Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…In the process of achieving the SDGs, the food supply chain still faces a number of challenges such as Blockchainembedded agricultural quality transparency, accountability, food scandals and inefficiencies in trust and information flow (Chandan et al, 2023). These issues affect consumers' trust in governments, certification bodies and food producers and their willingness to buy (Wang et al, 2022). Numerous scholars have studied the improvement of agricultural product quality by financial credit regulation such as green finance and agricultural credit.…”
Section: Credit Supervision Of Agricultural Product Quality and Safetymentioning
confidence: 99%
“…In the process of achieving the SDGs, the food supply chain still faces a number of challenges such as transparency, accountability, food scandals and inefficiencies in trust and information flow (Chandan et al ., 2023). These issues affect consumers' trust in governments, certification bodies and food producers and their willingness to buy (Wang et al ., 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Concerning circulation efficiency measurement, different scholars have used the Analytical Hierarchy Process (AHP), Data Envelopment Analysis (DEA), a super-efficiency model with undesirable outputs, and other methods to conduct their research (Su et al, 2019;Tošović-Stevanović et al, 2020;Guo and Li, 2022). Some scholars have conducted related research on the industry linkage effect of the APC service industry (Kim et al, 2021), the interactive development of logistics information services (Wang et al, 2019), and the dynamic relationship between influencing factors and APC efficiency (Wang et al, 2022;Liu, 2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, to meet the requirements of people of all countries for high-quality transnational agricultural food consumption upgrading and healthy diet, how to ensure agricultural products do not deteriorate or pollute during transportation and ensure the safety of agricultural products has attracted more and more attention and research [126]. Wang et al [127] found that blockchain technology positively impacts the qualification rate and circulation efficiency of agricultural food. Chen et al [128] proposed the contribution of Internet of Things technology to the cross-border agricultural food supply chain, which is of great significance for solving the safe and transparent management of fresh agricultural products and the traceability of production, transportation, and sales.…”
Section: Keyword Cluster Analysismentioning
confidence: 99%